Kerangka Konsep Modul Pengajaran Bahasa Arab Untuk Tujuan Teknologi - Muhammad Farhan Muhammad; Saipol Barin Ramli; Mohammad Taufiq Abdul Ghani; Amirul Nazri Mohamad; Mohammad Syahrul Naim Mohd Fauzi (USIM Press, 2024)
Vol. 6 No. 3 (2021): Special Issue